2012
DOI: 10.1089/vim.2011.0066
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus Immunogen That Provides Protective Tumor Immunity and Induces Tumor Regression

Abstract: Human papillomavirus (HPV) is associated with premalignant lesions such as high-grade cervical intraepithelial neoplasia (CIN-III) with potential progression to cervical carcinoma. There are now preventive vaccines against HPV. However, no effective therapeutic vaccine or immunological treatment exists for individuals already infected or for the 470,000 women that develop high-grade dysplasia, carcinoma in situ, and cervical cancer each year. More than half of these women die from cervical cancer. Relative non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…After re-vaccination at 1 year, Th1 responses remained, although enthusiasm for the re-vaccination was dampened by the Th2 cytokine response that also developed upon revaccination. In a study using a mouse HPV tumor model to assess both immunological and clinical responses, peptide mixtures of the HPV E7 oncogene were shown to stimulate both antibody and cellular immune responses reactive to HPV constructs and to limit tumor development [ 74 ]. While this latter study demonstrated the feasibility of HPV vaccine approaches to limit tumor development, it did not address the impact of vaccination on eliciting reactivity to premalignant lesions and their progression to cancer.…”
Section: Immunological Treatment Approaches For Premalignant Lesionsmentioning
confidence: 99%
“…After re-vaccination at 1 year, Th1 responses remained, although enthusiasm for the re-vaccination was dampened by the Th2 cytokine response that also developed upon revaccination. In a study using a mouse HPV tumor model to assess both immunological and clinical responses, peptide mixtures of the HPV E7 oncogene were shown to stimulate both antibody and cellular immune responses reactive to HPV constructs and to limit tumor development [ 74 ]. While this latter study demonstrated the feasibility of HPV vaccine approaches to limit tumor development, it did not address the impact of vaccination on eliciting reactivity to premalignant lesions and their progression to cancer.…”
Section: Immunological Treatment Approaches For Premalignant Lesionsmentioning
confidence: 99%